2014
DOI: 10.1186/1471-2482-14-48
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable materials for surgical management of infective endocarditis: new solution or a dead end street?

Abstract: BackgroundOne third of patients with infective endocarditis will require operative intervention. Given the superiority of valve repair over valve replacement in many indications other than endocarditis, there has been increasing interest and an increasing number of reports of excellent results of valve repair in acute infective endocarditis. The theoretically ideal material for valve repair in this setting is non-permanent, “vanishing” material, not at risk of seeding or colonization. The goal of this contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…However, when used without glutaraldehyde fixation, it shrinks, develops fibrosis and tends to stretch when exposed to high cardiovascular pressure, with reports of aneurysm formation at the site of the repair (13). The main advantage of glutaraldehyde fixation is that it improves the biostability of autologous and xenogeneic pericardium through collagen crosslinking, but with the potential consequences of residual toxic aldehydes which could result in late calcification (5,15). However, structural degeneration and dystrophic calcification remain limiting factors in terms of the longevity and clinical effectiveness of these bioprosthetic substitutes (11,12,16).…”
Section: Discussionmentioning
confidence: 99%
“…However, when used without glutaraldehyde fixation, it shrinks, develops fibrosis and tends to stretch when exposed to high cardiovascular pressure, with reports of aneurysm formation at the site of the repair (13). The main advantage of glutaraldehyde fixation is that it improves the biostability of autologous and xenogeneic pericardium through collagen crosslinking, but with the potential consequences of residual toxic aldehydes which could result in late calcification (5,15). However, structural degeneration and dystrophic calcification remain limiting factors in terms of the longevity and clinical effectiveness of these bioprosthetic substitutes (11,12,16).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the Kalangos-Bioring® dissolved within 6 months and was replaced by autologous fibrous tissue within 12 months in a juvenile pig model, and it allows the growth of the annulus within normal physiological limits [35]. On the other hand, a lack of blood contact due to a subendocardial implantation technique and replacement by a native fibrotic reactive tissue are important features of the BAR (Kalangos-Bioring®) that support its lower infection potential and its effect on long-term infection prevention [10,11,12,13,14]. In addition, in 2013, Daghighi et al [36] stated that the use of degradable biomaterials was a clinically effective strategy to reduce infection risk in the view of biomedical engineers.…”
Section: Discussionmentioning
confidence: 99%
“…A biodegradable annuloplasty ring (BAR) (Kalangos-Bioring®) is a tool mainly developed for pediatric heart operations and formed by a monofilament of biodegradable poly-1,4-dioxanone [8,9]. Its implantation technique and structure (intra-annular and nonporous, respectively) are different from those of the CAR, and these characteristics may increase its resistance to peri- and postoperative infections [10,11,12,13,14]. …”
Section: Introductionmentioning
confidence: 99%